Protocol for identifying protein synthesis activity in specific cell types of the testicular lumen - Dingfeng Zou; Kai Li; Yan Lu; Wei Yan; Wei Song (STAR Protocols)
Summary: Protein synthesis could control spermatogenic cell fate transitions. Here, we present a protocol for visualization and quantification of newly synthesized proteins by click-chemistry-based immunofluorescence within specific spermatogenic cell types in the mice testicular lumen. We detail the processes for O-propargyl-puromycin (OPP) incorporation, antibody incubation, confocal microscope imaging, and subsequent quantification methods. This protocol is not limited to spermatogenic cells and can be adapted to investigate protein synthesis in other testicular cell types and various tissue-specific cell populations.For complete details on the use and execution of this protocol, please refer to Zou et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.